2007
DOI: 10.4049/jimmunol.179.9.6204
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin Modulates Inflammatory Response and Neurotoxicity Induced by Microglial Activation

Abstract: Microglia are the major inflammatory cells in the brain. Recent studies have highlighted the reciprocal roles of other brain cells in modulating the microglial inflammatory responses. Urocortin (UCN) is a member of the corticotropin-releasing hormone (CRH) family of neuropeptides that function to regulate stress responses. In the present study, we demonstrated that expression of UCN in rat substantia nigra was found to be localized principally to dopaminergic neurons. In cell culture models, the CRH receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 61 publications
3
43
1
3
Order By: Relevance
“…As microglial cells express CRH receptors, 11 BDNF is one of the effector mediators released by microglial cells, 18 we hypothesized that spinal injury-derived CRH might activate microglial cells to release BDNF, which is further involved in neuron axon outgrowth. To prove this hypothesis, using the same rat model mentioned above, we assessed BDNF levels in the spinal cord.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As microglial cells express CRH receptors, 11 BDNF is one of the effector mediators released by microglial cells, 18 we hypothesized that spinal injury-derived CRH might activate microglial cells to release BDNF, which is further involved in neuron axon outgrowth. To prove this hypothesis, using the same rat model mentioned above, we assessed BDNF levels in the spinal cord.…”
Section: Resultsmentioning
confidence: 99%
“…11 Exogenous CRH can induce microglial cells to release inflammatory mediators and certain neural tissue responses such as inflammation. 10,11 Our results have extended these findings by showing that CRH has the capacity to drive microglial cells to release BDNF in response to spinal cord injury. Apart from inducing the undesired response, such as in stress-related disorders, 24 CRH can modulate behavior by enhancing the behavioral responses to stressors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in mesencephalic neuron-glia cultures, Ucn inhibited microglial activation and thus protected dopaminergic neurons against LPS-induced neurotoxicity. 43 Further studies in various inflammatory disease settings also suggested that Ucns could have a potential to function as endogenous anti-inflammatory factors. Ucn, a placental peptide, induced secretion of anti-inflammatory cytokines IL-4 and IL-10 from cultured human trophoblast cells isolated from the placentas and reversed LPS-induced TNF- release through the action of CRF 2 receptor.…”
Section: Corticotropin-releasing Factor Family and Its Receptors In Omentioning
confidence: 99%
“…These neuropeptides switch off the inflammatory response by regulating different critical levels of innate immunity (Chorny and Delgado, 2008;Chorny et al, 2008;Delgado et al, 2008a;Gonzalez-Rey et al, 2007a;Miksa et al, 2007;Wang et al, 2007): 1) they inhibit phagocytic activity, free radical production, adherence and migration of macrophages; 2) they reduce production of inflammatory cytokines (TNFα, and various chemokines by activated macrophages and microglia; 3) they downregulate expression of inducible nitric oxide synthase (iNOS) and cycloxygenase 2 (COX2) and the subsequent release of nitric oxide and prostanglandin E2 by macrophages, DCs and microglia; 4) they stimulate production of anti-inflammatory cytokines such as IL-10 and IL-1Ra; 5) they decrease co-stimulatory activity of antigen-presenting cells (APCs) for antigen-specific T cells by downregulating expression of co-stimulatory molecules; 6) they inhibit secretion of late inflammatory mediator highmobility group box 1 (HMGB1); 7) they reduce degranulation of mast cells; 8) they induce apoptosis in macrophages; and 8) they stimulate the peroxisome proliferator-activated receptor-γ (PPARγ), an anti-inflammatory-related transcription factor.…”
Section: Neuropeptides Counterbalance the Inflammatory Responsementioning
confidence: 99%